Analysis of the application of policy instruments for close-knit county medical communities based on Hood’s classification - Xianlu, Huang; Lei, Feng (Frontiers in Public Health, 2025)
ObjectiveBy analyzing the selection and application of policy instruments in the construction of close-knit county medical communities in Dazu District, Chongqing, this study aimed to propose countermeasures to optimize these policy instruments, offering valuable lessons for the construction of close-knit county medical communities.MethodsBased on Hood’s classification, an analytical framework was constructed that incorporated the selection of basic policy instruments (X dimension) and the different phases in the construction process (Y dimension). Nvivo was used to analyze policy documents (2015–2023) related to the construction of close-knit county medical communities in Dazu District.ResultsIn the X dimension, the nodality-based instruments accounted for 14.3%, the authority-based instruments accounted for 34.2%, the treasure-based instruments accounted for 16.4%, and the organization-based instruments accounted for 35.2%. In the Y dimension, the total number of policy instruments used in Dazu District across the following three phases—policy initiation, piloting, and promotion—showed an increasing trend, aligning with the number of policies. These statistics indicated several issues such as limited use of nodality-based and treasure-based instruments, an incomplete policy assessment indicator system, insufficient policy synergy and incentives, and a lack of operationalization of strategic measures.ConclusionThe government should increase the use of nodality-based and treasure-based instruments, improve the assessment indicator system, strengthen policy synergy mechanisms and incentives, and optimize the structure of talent resources to improve the operability of the policies.